Post Media Literacy: Menyaksikan Kuasa Media Bersama Michel Foucault - Iswandi Syahputra (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2010)
This article would like to present Michel Foucault’s idea concerning Knowledge and Power in media industry. As a contemporary intellectual, Foucault’s thought has a unique style of postmodernism. His thought had gone beyond traditional critical theory whose trying to disclose the relation of power and economic behind the ideology of media. Foucault’s thought had given new perspective in understanding how the media produce truth under tightly control process into something that seems normal. With the assumption of media has the power to create mass culture, which has to be studied critically by media literacy approach, Foucault’s thought had given new space of discursive. An alternative thought on how to estimate the work of mass media as supervisor of truth and creator of information trough normalization practice.